Muslim Nationalism: Iqbal’s Synthesis of Pan-Islamism and Nationalism (American Journal of Islam and Society, 1985)
Muhammad Iqbal (1877-1938) was a man of great many ideas-sublime and serene, dynamic and romatic, provocative and profound.He was both a great poet and a serious thinker; but in poetic works liesenshrined most of his thought. It seems rather platitudinous to say, but itis important to note, that a poet is essentially a man of moods, and enjoysa sort of poetic license which is scrupulously denied to a prose-writer.Since a poet usually gives utterance to his reactions to a given situation,his utterances and ideas need not always be compatible with one another.Such was the case with Iqbal.During his poetic career, spanning some four decades, Iqbal hadimbibed, approved, applauded and commended a great many ideas -ideas which occupied various positions along the spectrum on thephilosophic, social, and political plane. Thus, at one time or another, hecommended or denounced nationalism; propagated pan-Islamism andworld Muslim unity; criticised the West for its materialism, for its cutthroatcompetition and for its values while applauding the East for itsspiritualism and its concern for the soul; and condemned capitalismwhile preaching “a kind of vague socialism.”’ While, on the one hand, hesteadfastly stood for “the freedom of ijtihad with a view to rebuild thelaw of Shari’at in the light of modern thought and experience,” and evenattempted to reformulate the doctrines of Islam in the light of twentiethcentury requirements a la St. Augustine, he, on the other, also defendedthe orthodox position and the conservatism of Indian Islam on somecounts. Though “inescapably entangled in the net of Sufi thought," heyet considered popular mysticism or “the kind of mysticism whichblinked actualities, enervated the people and kept them steeped in allkinds of superstitions” as one of the primary causes of Muslim declineand downfall.It is to this aspect of Iqbal that Professor Hamilton A.R. Gibb wasreferring when he suggested: ...